Typification of Urban Green Spaces in the Assessment of Cultural Ecosystem Services (on the Example of Kyiv) - Корогода, Наталія Петрівна; Купач, Тетяна Геннадіївна; Ковтонюк, Ольга Володимирівна (Київський національний університет імені Тараса Шевченка, 2024)
Cultural ecosystem services (CES) are the benefits that urban populations receive from urban green spaces (UGS), supporting their health through interaction with the environment. Due to the dissimilarity of conditions in different UGSs, which can only be determined during a direct survey, the assessment of CES is quite complex. Analysis of the factors affecting the volume of CES allows for the typing and grouping of UGSs with similar characteristics. This makes it possible to extrapolate the survey data from key areas to all green spaces of a particular kind. The purpose of the study is to develop a typification of urban green spaces for the assessment of CES. The assessment should be based not only on perception indicators, but also take into account the current state of green spaces. The objectives of the study are as follows: to take into account the natural and anthropogenic characteristics that determine the potential of green spaces to provide CES; to typify green spaces based on these characteristics; to substantiate a set of key areas whose research data would objectively reflect the potential of UGS to provide CES on the example of Kyiv. The basis for the allocation of three classes of UGS was the general classification of green spaces by functional feature. Such a division was used because it takes into account, on the one hand, the accessibility of the green space, and, on the other hand, the presence of characteristics that are used as calculation parameters in the CES assessment. Ecological zoning of territory became the basis for the allocation of 8 types of UGS in the CES assessment. After all, green areas of the same class can provide different amounts of CES, given the different perception of their natural features. The perception of different types of forests necessitated the division of such a type as "forest and forest park areas" into kinds. This, as well as the need to take into account the "age" of the green space and/or the building area in which it is located, led to the identification of 13 kinds of UGS. Based on this typification, a set of 63 key areas was identified, the data of which objectively reflect the potential of different kinds of UGS to provide CES. The data obtained within these sites are representative of other UGSs within the same kind.

Складність оцінки культурних екосистемних послуг (КЕП) виникає через несхожість умов у різних міських зелених зонах (МЗЗ), які можна визначити лише під час безпосереднього обстеження. Аналіз чинників, що впливають на обсяги КЕП, дозволяє типізувати та згрупувати МЗЗ зі схожими у мовами. Це створює можливість екстраполювати дані обстеження ключових ділянок на всі зелені зони окремого виду. Метою роботи є розробка типізації зелених зон міста для оцінки КЕП. Завданнями роботи стали: визначення характеристик, що зумовлюють потенціал зелених зон у наданні КЕП; проведення типізації зелених зон з урахуванням даних характеристик; обґрунтування набору ключових ділянок на прикладі м. Києва. В основу виділення трьох класів МЗЗ було покладено загальну класифікацію зелених зон за функціональною ознакою.  Екологічне зонування території стало основою для виділення 8 типів МЗЗ у оцінці КЕП. Сприйняття різних типів лісу, обумовило необхідність поділу такого типу як «лісові та лісопаркові масиви» на види. Це, а також необхідність врахування «віку» зеленої зони та/або масиву забудови, у якому вона розташована обумовили виділення 13 видів МЗЗ. На основі проведеної типізації було  обґрунтовано набір з 63 ключових ділянок у межах Києва. Дані, отримані у межах цих ділянок є репрезентативними для інших МЗЗ у межах виду.
Типізація зелених зон міста в оцінці культурних екосистемних послуг (на прикладі міста Києва)
Keywords: urban green spaces; typing of green spaces; cultural ecosystem services; міські зелені зони; типізація зелених зон; культурні екосистемні послуги